Clinical study of factors associated with pregnancy outcomes in pregnant women with systemic lupus erythematosus in the southern China - Ke Zhang,; Chunmei He,; Qiaoting Deng,; Wengen Li,; Zhixiong Zhong,; Jingyuan Hou, (Archives of Rheumatology, 2022)
Objectives: This study aims to estimate predicted factors for maternal and fetal outcomes in Hakka pregnant women with systemic lupus erythematosus (SLE) in the southern China. Patients and methods: Between June 2014 and February 2020, we retrospectively analyzed the data of a total of 123 singleton pregnant women with SLE (mean age: 27.1±4.1 years; range, 19 to 39 years) who were referred to our rheumatology clinic. Demographic, clinical, and laboratory data of the patients were recorded. Adverse pregnancy outcomes (APOs) were assessed. Results: Multivariate logistic regression analysis revealed that preeclampsia was associated with the increased odds of APOs (odds ratios [OR]=9.538, 95% confidence interval [CI]: 2.055-44.271, p=0.004), premature birth (OR=14.289, 95% CI: 3.596-56.777, p<0.001) and low birth weight (OR=8.275, 95% CI: 2.117-32.345, p=0.002). Anti-double-stranded deoxyribonucleic acid (anti-dsDNA) antibody positivity was the predictor of APOs (OR=2.165, 95% CI: 1.034-4.532, p=0.040), premature birth (OR=2.849, 95% CI: 1.220-6.657, p=0.016) and pregnancy loss (OR=3.004, 95% CI: 1.086-8.305, p=0.034). The use of hydroxychloroquine and prednisone was associated with the decreased odds of APOs (OR=0.412, 95% CI: 0.198-0.860, p=0.018) and pregnancy loss (OR=0.304, 95% CI: 0.111-0.831, p=0.020). Conclusion: Our study results indicate that preeclampsia, anti-dsDNA antibody positivity, and the use of hydroxychloroquine and prednisone are independent predictors of pregnancy outcomes.